Analisis Perilaku Bullying yang Dialami Anak Jalanan (Studi Kasus pada Anak Jalanan di Kota Padang) - Farah Fadhilah; Netrawati Netrawati (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
The problem that will be studied in this research is the types of bullying experienced by street children in the city of Padang. Street children are children who are forced to take to the streets due to several factors. The situation of street children is sometimes exacerbated by violence. Violence that occurs in the child's environment can be referred to as bullying. Bullying does not only occur in educational environments, but can also occur on the streets. This type of qualitative research with the case study method. Sources of data from street children as research subjects and research informants. Data collection methods used are interviews and observation. The data analysis technique refers to Miles and Huberman's interactive analysis model. To test the validity of the data used triangulation techniques with sources. The results showed that the type of bullying experienced by street children was direct bullying in the form of being beaten, pushed, tripped over, stoned, teased, humiliated, grabbed, compassed, pulled by his clothes, cursed at and slapped. For this type of indirect bullying in the form of being ostracized from social groups, spreading gossip, being insulted via the internet and being threatened via the internet.